Odarchenko’s Poems: Interactions of Surrealism, Surrealist Code, and Sentimentalism - Oleg S. Gorelov (Studia Litterarum)
The article examines surrealist codes in poetry on the example of Y. Odarchenko’s poems. The signs of these codes include: peculiar sentimental tone; rationalist approach to the use of language; plotted poetic diegesis and poeticized prose; and principle of metonymic displacements. In the texts of Odarchenko, grotesque artistic optics leads to multilateral shifts: in terms of intonation — a shift from sentimentality to black humor; in term of genre —a shift from the idyll to horror; at the composition level — a shift from the detailed description of minor and largely random details to a pointe that highlights some underlying terrible pattern. It is possible to interpret sentimentality and lyrical tone of the poem as a response to what the poet himself believes to be another magical world while others fail to spot the coexistence of two worlds penetrating each other. While the penetration of the real and imaginary worlds develops into a Sternian motif of the wound, it also evokes surrealistic attention to the world and its living creatures.